2012
DOI: 10.1016/j.chom.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Structure-Function Analysis Reveals the Pathogenic Signaling Potentiation Mechanism of Helicobacter pylori Oncogenic Effector CagA

Abstract: The Helicobacter pylori type IV secretion effector CagA is a major bacterial virulence determinant and critical for gastric carcinogenesis. Upon delivery into gastric epithelial cells, CagA localizes to the inner face of the plasma membrane, where it acts as a pathogenic scaffold/hub that promiscuously recruits host proteins to potentiate oncogenic signaling. We find that CagA comprises a structured N-terminal region and an intrinsically disordered C-terminal region that directs versatile protein interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
194
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(210 citation statements)
references
References 46 publications
11
194
0
5
Order By: Relevance
“…In this study, we found that multiple domains of CagA are also responsible for Snail stabilization and that the C-terminus of CagA having the EPIYA motif binds to 38). Considering that a dynamic CagA structure having a-helices and undergoing activation of the Wnt/EMT process depends on more than EPIYA phosphorylation 26,29,45 , it is not surprising that many domains of CagA are able to bind GSK-3, resulting in depletion of GSK-3 and subsequent increased Snail protein abundance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we found that multiple domains of CagA are also responsible for Snail stabilization and that the C-terminus of CagA having the EPIYA motif binds to 38). Considering that a dynamic CagA structure having a-helices and undergoing activation of the Wnt/EMT process depends on more than EPIYA phosphorylation 26,29,45 , it is not surprising that many domains of CagA are able to bind GSK-3, resulting in depletion of GSK-3 and subsequent increased Snail protein abundance.…”
Section: Discussionmentioning
confidence: 99%
“…that EPIYA motif phosphorylation plays important roles in entire CagA structure and protein interactions 29 . In this study, we found that multiple domains of CagA are also responsible for Snail stabilization and that the C-terminus of CagA having the EPIYA motif binds to 38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les cellules LLC-B ont un mĂ©tab olisme plus actif que les cellules saines, ce qui entraĂźne une production plus importante de radicaux libres et une dĂ©pendance vis-Ă -vis des antioxydants cellulaires comme le glutathion (GSH) pour maintenir leur balance redox intracellulaire [8,9]. De plus, l'interaction des cellules LLC-B avec les cellules accessoires (cellules stromales, cellules nurse-like) dans la moelle osseuse ou les ganglions est aussi importante pour leur survie [10,11]. En effet, les cellules leucĂ©miques expriment Ă  leur surface le rĂ©cepteur de chĂ©mokines CXCR4 RĂ©sistance des cellules de LLC Ă  l'apoptose…”
Section: Resultsunclassified